2012
DOI: 10.2304/plat.2012.11.2.228
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Undergraduate Positive Psychology: An Active Learning Approach Using Student Blogs

Abstract: In just over ten years positive psychology has become a major subfield in psychology. This is reflected in the development of positive psychology courses at many universities and in over a thousand empirical articles published in peer-reviewed journals. Thus far, there is little published research suggesting ways to incorporate active learning techniques into these courses. This article describes the use of student blogs, employing a university blog platform, to teach several interventions in an undergraduate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…Among university students, three studies were found. Bridges et al (2012) described a methodology of intervention among psychology students enrolled in a course in Positive Psychology. Using a university blog platform as a marketing tool, the authors asked the students to complete three exercises, known as Three Good Things (at the end of each day for three weeks, remember three good things that happened); Strengths (using one of the main strengths in a new and different way every day for one week and leave a record of these activities on the blog) and the Gratitude letter (to write a letter of gratitude to someone who has been a positive influence).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among university students, three studies were found. Bridges et al (2012) described a methodology of intervention among psychology students enrolled in a course in Positive Psychology. Using a university blog platform as a marketing tool, the authors asked the students to complete three exercises, known as Three Good Things (at the end of each day for three weeks, remember three good things that happened); Strengths (using one of the main strengths in a new and different way every day for one week and leave a record of these activities on the blog) and the Gratitude letter (to write a letter of gratitude to someone who has been a positive influence).…”
Section: Discussionmentioning
confidence: 99%
“…Using a university blog platform as a marketing tool, the authors asked the students to complete three exercises, known as Three Good Things (at the end of each day for three weeks, remember three good things that happened); Strengths (using one of the main strengths in a new and different way every day for one week and leave a record of these activities on the blog) and the Gratitude letter (to write a letter of gratitude to someone who has been a positive influence). As a result of the course evaluation on a seven-point scale, which is required by the university, the students gave a significantly higher assessment of the Positive Psychology course that used the blog, both in the quality of the course and the teacher who administered classes, compared with the previous two semesters without the use of the blog (Bridges et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a recent study, which only included 50–70 year old German-speaking participants and the same instructions and design as in the Gander et al (2013) study, there were effects for happiness (at all post measures), but for depressive symptoms only for the post-test and the 1 month measure (Proyer et al, 2014). Other studies have found effects for SS-interventions for personal well-being as well as an engaged and pleasurable life (Mitchell et al, 2009), and life satisfaction (Duan et al, 2013; see also Bridges et al, 2012). Furthermore, harmonious passion seems to be a moderator of the effectiveness of the intervention on well-being (Forest et al, 2012), whereas extraversion was identified as a moderator of the interventions’ effects on depressive symptoms (Senf and Liau, 2013).…”
Section: Introductionmentioning
confidence: 95%